Materanal and neonatal outcomes of triplet gestation in a tertiary care centre: a retrospective study - Sharma, Neeraj; Kumari, Deepika; Prasad, Sonal; Srivastava, Akanksha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: A significant rise in triplet pregnancy rate has occurred recently. This rise is of concern, as these infants are frequently reported as a risk factor of adverse outcome. The aim of this study was to retrospectively study the outcomes of triplet births. Methods: A retrospective study was undertaken to analyze the clinical data of all patients with triplet gestation admitted to the labour room of Dr. Baba Saheb Ambedkar Hospital, Delhi to study the maternal and fetal outcomes. Authors retrospectively observed and analyzed the database to examine triplet gestations delivered between January 2014 and December 2018. Results: Over the five-year study period, there were total 44,011 deliveries. Out of these, there were 35 (0.079%) triplet pregnancies. Of all the triplet pregnancies studied 80% resulted from ovulation induction and assisted reproductive technology. The mean gestational age at delivery was 31.6±3.0 weeks, and the mean birth weight was 1,594±460 gm. The most common maternal complications were Preterm labour in 32 pregnancies (92%), anemia in 17 (49%), pre-eclampsia in 11 (31%), post-partum hemorrhage in 8 (22%). Of the total deliveries neonatal complications included Respiratory distress syndrome in 44 (42.2%), Hyperbilirubinemia in 41 (39%), Intrauterine growth restriction in 19 (18.1%). The perinatal mortality rate was 10.5%. Conclusions: Higher order pregnancies are associated with maternal and neonatal complications. These high risk women need more care and the neonates require intensive care and monitoring after birth, most commonly due to prematurity and low birth weight.